Total English Pre-intermidiate. Students Book - Acklam, Richard and Crace, Araminta (Harlow Pearson Education Limited, 2008)
Total English is a new course for young adults and adults. It provides solutions to the challenges teachers and students face every day with a complete package of effective, easy-to0use resources.
Keywords: English Practice